An in vivo evaluation of the potential of 188Re-PEI-MP for therapy of bladder carcinoma and 99mTc-PEI-MP for diagnosis and follow up - Ferreira, Sara (2015)
The development of water-soluble polymers such as PEI-MP (polyethyleneimine, functionalised with methylphosphonate groups) that might be labeled with 188Re (emits of high energy beta particles) and 99mTc are recent approaches, with a strong potential for metabolic radiotherapy and diagnosis, respectively. The aim of this study was to evaluate the efficacy of 188Re-PEI-MP as therapeutic agent for bladder carcinoma and 99mTc-PEI-MP for its diagnosis and follow up.